Molecular Detection of Influenza A virus in Domestic Ducks and Geese in Basra Province, Southern Iraq - T. Mansour, Firas; T. Thwiny, Hazim; A. Najim, Harith (University of Thi-Qar Journal of Science, 2019)
Avian influenza is one of the important viral diseases in poultry that can cause serious economic losses in many countries around the world, and occasionally infect human causing mild to severe illness. It is caused by avian influenza A viruseswhich have been isolated from avian species, particularly waterfowls that are considered the main reservoir for all influenza A virus subtypes. The aim of this study was to detect influenza virus from domestic ducks and geese in different geographical regions(Abu Al-Khasseb, Shatt Al-Arab, Zubair, and Al-Qurnah) of Basrah province, Southern Iraq. The study was conducted on 115 cloacal swabs collected from 60 ducks and 55 geese distributed in different regions of Basrah province. Samples were processed for RT-PCR to amplify matrix (M) gene that is conserved between all influenza A subtypes by using a set of universal primer. We demonstrated that influenza A viruses is prevalent in domestic waterfowls with a significantly higher percentage in ducks than geese; 42 samples (29 ducks and 13geese) were positive to viral M gene. In addition, the virus prevalence was significantly higher in the North of Basrah (Al-Qurnah region) than the other geographical regions. The overall findings of this study obtained a primary picture about the distribution of avian influenza viruses in our region, which is importantto prevent the spread of infection to poultry and eventually minimize the risk of acquiring infection to humans. According toour knowledge, this is the first study aimed to identify avian influenza viruses in waterfowls in Basrah province, Southern Iraq.